Market Revitalization Policy Reviewed from GOOD GOVERNANCE’S Perspective (A Study at Dinoyo Market of Malang) - Muhammad Mardani; Ratih Nur Pratiwi; Siti Rochmah (Sekolah Pascasarjana Universitas Brawijaya, 2021)
As one of the cities that carries Tri Bina Cita, the city of students, industry, and tourism, it’s undeniable that Malang City has become one of the strategic areas in the development of modern markets. Through the development of modern markets in Malang City, it’s possible that people tend to switch from traditional markets to modern markets. Therefore, to keep pace with market growth expected in Malang City, it’s fitting traditional markets to be addressed through a policy, which is market revitalization. Market revitalization can be interpreted as a process, method, and action that is able to give importance to sellers and buyers in traditional market. The implementation of market revitalization should be done to balance the growth rate of modern market in an area. Market Revitalization Dinoyo governance aims to regulate the market, so it will be more organized, orderly, and convenient for sellers and buyers.The revitalization policy at Dinoyo Market is a form of decision implemented by Malang City Government, as an effort to increase the competitiveness of traditional markets in Malang City, such as Dinoyo Market. The revitalization at Dinoyo Market not just talking about the construction, but the real impact that can be felt by the public, as sellers and buyers at Dinoyo Market. Some of the things that must be considered by Malang City Government regarding the revitalization policy at Dinoyo Market is about the feasibility of market buildings, which became a part of the protection for the sellers and buyers at Dinoyo Market, also market safety, to provide convenience to visitors who shop at Dinoyo Market, furthermore cleanliness of market location and hygiene ingredients at Dinoyo Market, to ensure these materials are protected from things that are dangerous and safe for consumption. Therefore, this study will discuss about the revitalization policy at Dinoyo Market through the perspective of Good Governance, so that it can find out the efforts that have been made and can be carried out by Malang City Government.